Interface modification method for preparing all-solid-state thin film energy storage device
The lithium phosphate/lithium oxide composite buffer layer is formed on the surface of lithium phosphate and oxygen nitride through oxygen plasma treatment, which solves the problem of incompatibility between lithium phosphate and oxygen nitride and the anode interface, and achieves the performance improvement and thermal stress reduction of all-solid-state thin-film energy storage devices.
Patent Information
- Application Number
- CN202411787548.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-11
AI Technical Summary
The interface incompatibility between lithium phosphooxynitride and the anode leads to a reduced performance of all-solid-state thin-film energy storage devices. The existing buffer layer materials are difficult to meet the requirements of chemical stability, mechanical stability, ionic conductivity and electronic conductivity at the same time. The commonly used interface modification methods require high-temperature annealing, resulting in thermal stress problems.
The lithium phosphate/lithium oxide composite film is formed on the surface of lithium phosphate nitride by oxygen plasma treatment as a buffer layer, and the composite buffer layer is formed at room temperature by using the strong reactivity of the oxygen plasma, avoiding the thermal stress problem caused by high-temperature annealing.
Interface modification of the lithium phospho-oxynitride surface is realized, forming a composite buffer layer with excellent chemical and mechanical stability, high ionic conductivity and low electron conductivity, effectively reducing the interface impedance between the lithium phospho-oxynitride and the anode, promoting ion migration and suppressing electron transport and leakage.
Smart Images

Figure CN119797774A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage device preparation, and in particular to an interface modification method for preparing an all-solid-state thin-film energy storage device. Background Art
[0002] All-solid-state thin-film energy storage devices (including all-solid-state thin-film batteries, all-solid-state thin-film supercapacitors, etc.) have the advantages of high energy density, high power density, and low leakage, and are very suitable for powering microsystems. Electrolyte films play a vital role in all-solid-state thin-film energy storage devices. Among them, lithium phosphorus oxynitride (LiPON) electrolytes and their derivatives still play a leading role in all-solid-state thin-film energy storage devices because of their good electrochemical, electrical, and mechanical properties. However, the interface incompatibility between lithium phosphorus oxynitride and the anode greatly reduces the performance of all-solid-state thin-film energy storage devices.
[0003] At present, the methods for improving the interface mainly focus on inserting a buffer layer between the lithium phosphorus oxynitride / anode interface. The ideal buffer layer should have: good chemical stability to inhibit adverse element diffusion and interface reaction; good mechanical stability to avoid damage caused by stress caused by volume expansion during device operation; high ionic conductivity to promote ion migration; low electronic conductivity to inhibit self-leakage. Unfortunately, it is difficult to find a material that meets all of the above requirements. Taking two commonly used buffer materials (lithium phosphate and lithium oxide) as an example, lithium phosphate has good chemical stability and relatively high ionic conductivity, but relatively low mechanical stability, which is not conducive to the life of the device; in contrast, lithium oxide has good mechanical strength and ultra-low electronic conductivity, but low ionic conductivity, which is not conducive to ion transmission, which will reduce the capacity and rate performance of the device. In addition, the interface modification methods currently used usually require operations such as high-temperature annealing, which will cause high thermal stress, thereby affecting the yield, compatibility and performance of the device. Summary of the invention
[0004] The present invention provides an interface modification method for preparing an all-solid-state thin-film energy storage device, wherein a lithium phosphate / lithium oxide composite film is formed on the surface of lithium phosphorus oxynitride by oxygen plasma treatment as a buffer layer between the lithium phosphorus oxynitride / anode interface, thereby effectively reducing the interface impedance of the lithium phosphorus oxynitride and inhibiting the transmission of electrons between electrolytes.
[0005] The embodiment of the present invention provides an interface modification method for preparing an all-solid-state thin film energy storage device, comprising the following steps:
[0006] Step 1, sputtering a layer of platinum on a clean substrate;
[0007] Step 2, sputtering a layer of lithium phosphorus oxynitride on the surface of the platinum layer obtained in step 1;
[0008] Step 3, treating the surface of the lithium phosphorus oxynitride obtained in step 2 with oxygen plasma, thereby forming a lithium phosphate / lithium oxide composite buffer layer on the surface of the lithium phosphorus oxynitride;
[0009] Step 4, sputtering a layer of platinum on the surface of the lithium phosphate / lithium oxide composite buffer layer obtained in step 3.
[0010] Optionally, in one embodiment of the present invention, in step 3, the thickness of the lithium phosphate / lithium oxide composite buffer layer is 3-10 nm.
[0011] Optionally, in one embodiment of the present invention, in step 3, the power of the oxygen plasma treatment is 15-40 W, and the flow rate is 5-30 sccm.
[0012] The interface modification method for preparing an all-solid-state thin film energy storage device according to the embodiment of the present invention has the following beneficial effects:
[0013] 1. The interface modification method of the surface of the electrolyte layer treated with oxygen plasma proposed in the present invention can form a lithium phosphate / lithium oxide composite buffer layer on the surface of lithium phosphorus oxynitride, so that the solid electrolyte has excellent chemical and mechanical stability, high ionic conductivity and low electronic conductivity.
[0014] 2. Advantages of oxygen plasma treatment: It is compatible with semiconductor processes and does not require high temperatures compared to conventional treatment processes (high temperature annealing). Therefore, low temperature and low stress can achieve modification and regulation of the electrolyte interface.
[0015] 3. Compared with single buffer layers such as lithium phosphate or lithium oxide, the oxygen plasma treatment process can generate a composite buffer layer in one step. The process is simple, and the generated composite buffer layer draws on the advantages of both lithium phosphate and lithium oxide and avoids their disadvantages. The composite buffer layer has the advantages of high lithium ion conductivity, high chemical stability, high mechanical properties, low electronic conductivity, etc.
[0016] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0018] Figure 1 A flow chart of an interface modification method for preparing an all-solid-state thin film energy storage device provided according to an embodiment of the present invention;
[0019] Figure 2A schematic diagram of the structure of lithium phosphorus oxynitride prepared in Example 1 of the present invention;
[0020] Figure 3 A schematic diagram of the structure of lithium phosphorus oxynitride treated with oxygen plasma prepared in Example 2 of the present invention;
[0021] Figure 4 A schematic diagram of the structure of lithium phosphorus oxynitride treated with oxygen plasma prepared in Example 3 of the present invention;
[0022] Figure 5 is the interface impedance of lithium phosphorus oxynitride at different temperatures in an embodiment of the present invention;
[0023] Figure 6 FIG. 1 is a graph showing the change of the electron current of lithium phosphorus oxynitride over time according to an embodiment of the present invention. DETAILED DESCRIPTION
[0024] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0025] Figure 1 The present invention is a flowchart of an interface modification method for preparing an all-solid-state thin film energy storage device according to an embodiment of the present invention.
[0026] like Figure 1 As shown, the interface modification method for preparing an all-solid-state thin film energy storage device comprises the following steps:
[0027] Step 1: sputter a layer of platinum (Pt) on a clean substrate.
[0028] Step 2: sputtering a layer of lithium phosphorus oxynitride (LiPON) on the surface of the platinum layer obtained in step 1.
[0029] Step 3: treating the surface of the lithium phosphorus oxynitride obtained in step 2 with oxygen plasma, thereby forming a lithium phosphate / lithium oxide composite buffer layer on the surface of the lithium phosphorus oxynitride.
[0030] Step 4, sputtering a layer of platinum on the surface of the lithium phosphate / lithium oxide composite buffer layer obtained in step 3.
[0031] Optionally, in one embodiment of the present invention, the thickness of the lithium phosphate / lithium oxide composite buffer layer in step 3 is 3-10 nm. If the thickness is too thin, the buffer layer cannot function, and if the thickness is too thick, the electrolyte will be deteriorated. The thickness of the interface buffer layer can be adjusted by adjusting the plasma treatment time, which is about 1-5 minutes, which is related to the power and flow rate of the oxygen plasma treatment.
[0032] Optionally, in one embodiment of the present invention, the power of the oxygen plasma treatment in step 3 is 15-40W and the flow rate is 5-30sccm. If the power or flow rate is too small, it is not enough to produce the interface buffer layer; if the power or flow rate is too large, the plasma will etch and damage the electrolyte layer.
[0033] Due to the strong reactivity of oxygen plasma, through appropriate plasma treatment, the nitrogen on the surface of lithium phosphorus oxynitride will be replaced by oxygen, resulting in the formation of a lithium phosphate / lithium oxide composite buffer layer. This lithium phosphate / lithium oxide composite buffer layer inherits the advantages of lithium oxide (including good mechanical strength and ultra-low electronic conductivity) and lithium phosphate (including good chemical stability and relatively high ionic conductivity), and has excellent chemical and mechanical stability, high ionic conductivity and low electronic conductivity, so it is very suitable as a buffer layer between the lithium phosphorus oxynitride / anode interface. This buffer layer will effectively suppress the incompatibility of the lithium phosphorus oxynitride / anode interface, thereby greatly reducing the interface impedance between the lithium phosphorus oxynitride and the anode, thereby facilitating ion migration and suppressing the transmission of electrons between the two and leakage. It should be pointed out that due to the strong reactivity of oxygen plasma, the above process can be carried out at room temperature, thereby avoiding the negative effects of high temperature in the existing method.
[0034] The interface modification method for preparing an all-solid-state thin film energy storage device of the present invention is described in detail below through specific embodiments and drawings.
[0035] Example 1
[0036] like Figure 2 As shown, an interface modification method for preparing an all-solid-state thin film energy storage device comprises the following steps:
[0037] Step 1: ultrasonically clean the substrate with acetone, anhydrous ethanol and deionized water for 5 minutes in sequence;
[0038] Step 2: Prepare a platinum layer with a thickness of 80-150 nm on the upper surface of the glass substrate as a current collector by sputtering, wherein the sputtering target is platinum, the sputtering power is 85 W, and the argon gas flow rate is 25.0 sccm;
[0039] Step 3: Prepare a lithium phosphorus oxynitride layer with a thickness of 700-1000 nm on the surface of the platinum layer obtained in step 2 by a sputtering process, wherein the sputtering target is lithium phosphate, the sputtering power is 130 W, and the nitrogen flow rate is 13.4 sccm;
[0040] Step 4: Prepare a platinum layer with a thickness of 80-150 nm as a current collector on the upper surface of the lithium phosphorus oxynitride layer obtained in step 3 by a sputtering process, wherein the sputtering target is platinum, the sputtering power is 85 W, and the argon gas flow rate is 25.0 sccm.
[0041] Example 2
[0042] The difference between Example 2 and Example 1 is that the surface of the lithium phosphorus oxynitride layer is treated with oxygen plasma to produce a lithium phosphate / lithium oxide composite buffer layer with a moderate thickness. The other aspects are the same as Example 1, such as Figure 3 As shown, an interface modification method for preparing an all-solid-state thin film energy storage device comprises the following steps:
[0043] Step 1: ultrasonically clean the substrate with acetone, anhydrous ethanol and deionized water for 5 minutes in sequence;
[0044] Step 2: Prepare a platinum layer with a thickness of 80-150 nm on the upper surface of the glass substrate as a current collector by sputtering, wherein the sputtering target is platinum, the sputtering power is 85 W, and the argon gas flow rate is 25.0 sccm;
[0045] Step 3: Prepare a lithium phosphorus oxynitride layer with a thickness of 700-1000 nm on the surface of the platinum layer obtained in step 2 by a sputtering process, wherein the sputtering target is lithium phosphate, the sputtering power is 130 W, and the nitrogen flow rate is 13.4 sccm;
[0046] Step 4: Form a lithium phosphate / lithium oxide composite film with a thickness of 3-10 nm as a buffer layer of the phosphorus oxynitride layer on the upper surface of the phosphorus oxynitride layer obtained in step 3 by oxygen plasma treatment technology, wherein the power is 20 W, the flow rate is 15 sccm, and the duration is 2 minutes;
[0047] Step 5: Prepare a platinum layer with a thickness of 80-150 nm as a current collector on the upper surface of the lithium phosphate / lithium oxide composite buffer layer obtained in step 4 by a sputtering process, wherein the sputtering target is platinum, the sputtering power is 85 W, and the argon gas flow rate is 25.0 sccm.
[0048] Example 3
[0049] The difference between Example 3 and Example 2 is that the oxygen plasma treatment conditions for the surface of the lithium phosphorus oxynitride layer are different, the buffer layer thickness is thicker and the composition is different from that of Example 2. Others are the same as Example 2, such as Figure 4As shown, an interface modification method for preparing an all-solid-state thin film energy storage device comprises the following steps:
[0050] Step 1: ultrasonically clean the substrate with acetone, anhydrous ethanol and deionized water for 5 minutes in sequence;
[0051] Step 2: Prepare a platinum layer with a thickness of 80-150 nm on the upper surface of the glass substrate as a current collector by sputtering, wherein the sputtering target is platinum, the sputtering power is 85 W, and the argon gas flow rate is 25.0 sccm;
[0052] Step 3: Prepare a lithium phosphorus oxynitride layer with a thickness of 700-1000 nm on the surface of the platinum layer obtained in step 2 by a sputtering process, wherein the sputtering target is lithium phosphate, the sputtering power is 130 W, and the nitrogen flow rate is 13.4 sccm;
[0053] Step 4: Form a lithium oxide layer with a thickness of 10-20 nm as a buffer layer of the phosphorus oxynitride layer on the upper surface of the phosphorus oxynitride layer obtained in step 3 by oxygen plasma treatment technology, wherein the power is 20 W, the flow rate is 45 sccm, and the duration is 2 minutes;
[0054] Step 5: Prepare a platinum layer with a thickness of 80-150 nm as a current collector on the upper surface of the lithium oxide layer obtained in step 4 by a sputtering process, wherein the sputtering target is platinum, the sputtering power is 85 W, and the argon gas flow rate is 25.0 sccm.
[0055] like Figure 5 and Figure 6 Shown are the changes in the interface impedance of lithium phosphorus oxynitride and the electronic current of lithium phosphorus oxynitride over time at different temperatures in Example 1, Example 2 and Example 3.
[0056] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or N embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0057] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, "N" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0058] Any process or method description in a flowchart or otherwise described herein may be understood to represent a module, fragment or portion of code comprising one or N executable instructions for implementing the steps of a custom logical function or process, and the scope of the preferred embodiments of the present application includes alternative implementations in which functions may not be performed in the order shown or discussed, including performing functions in a substantially simultaneous manner or in reverse order depending on the functions involved, which should be understood by technicians in the technical field to which the embodiments of the present application belong.
Claims
1. An interface modification method for preparing an all-solid-state thin film energy storage device, characterized in that: The following steps are involved: Step 1, sputtering a layer of platinum on a clean substrate; Step 2, sputtering a layer of lithium phosphorus oxynitride on the surface of the platinum layer obtained in step 1; Step 3, treating the surface of the lithium phosphorus oxynitride obtained in step 2 with oxygen plasma, thereby forming a lithium phosphate / lithium oxide composite buffer layer on the surface of the lithium phosphorus oxynitride; Step 4, sputtering a layer of platinum on the surface of the lithium phosphate / lithium oxide composite buffer layer obtained in step 3.
2. The method according to claim 1, characterized in that: In step 3, the thickness of the lithium phosphate / lithium oxide composite buffer layer is 3-10 nm.
3. The method according to claim 1, characterized in that In step 3, the power of oxygen plasma treatment is 15-40 W and the flow rate is 5-30 sccm.